Granite crags - Gordon Cumming, C. F. (Constance Frederica), 1837-1924. (Edinburgh, London, W. Blackwood and sons, 1884)
Constance Frederica Gordon-Cumming (1837-1924) was an Englishwoman who sailed from Tahiti to San Francisco in April 1878 and remained in California for five months. Granite crags (1884) is a volume of her travel letters detailing visits to San Rafael, the redwood forsets, the San Joaquín and Sacramento Valleys, Yosemite, Oakland, and Tulare Lake. She evinces great interest in hydraulic mining operations and quartz mining near Sonora and the Stanislaus River and gives special attention to the region's botany and agriculture as well as recounting tales of the Gold Rush and San Francisco in the lawless 1850s.
Travels in California.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel; Yosemite Valley (Calif.); Law -- Political aspects -- California; Mines and mineral resources -- California; Agriculture -- California; Business -- California